1997
DOI: 10.1097/00004714-199710000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Comparison of Olanzapine Versus Risperidone in the Treatment of Schizophrenia and Other Psychotic Disorders

Abstract: Olanzapine and risperidone, both second-generation antipsychotic agents, represent two different pharmacologic strategies. Although they share some in vitro properties, they differ by virtue of their chemical structure, spectrum of receptor binding affinities, animal neuropharmacology, pharmacokinetics, and in vivo neuroimaging profile. Based on such differences, it was hypothesized that the two compounds would show distinct safety and/or efficacy characteristics. To test this hypothesis, an international, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
325
5
15

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 651 publications
(380 citation statements)
references
References 33 publications
32
325
5
15
Order By: Relevance
“…The improvement of psychopathology, especially the PANSS negative score during the trial, is remarkable but not completely unusual. Similar longitudinal investigations reported comparable findings (Tran et al, 1997;Peuskens et al, 1999). Others, however, showed much smaller changes in stable outpatients or first-episode patients (eg Hirsch et al, 2002;Lieberman et al, 2003).…”
Section: Panss Scoresupporting
confidence: 64%
See 1 more Smart Citation
“…The improvement of psychopathology, especially the PANSS negative score during the trial, is remarkable but not completely unusual. Similar longitudinal investigations reported comparable findings (Tran et al, 1997;Peuskens et al, 1999). Others, however, showed much smaller changes in stable outpatients or first-episode patients (eg Hirsch et al, 2002;Lieberman et al, 2003).…”
Section: Panss Scoresupporting
confidence: 64%
“…The dropout rates of patients during the study of 25% (T12) or 40% (T24), respectively, were within the expected range of such longterm trials. In two double-blind multicenter studies with schizophrenic patients over 28 weeks dropout rates of 40 or 55%, respectively, were reported (Tran et al, 1997;Hirsch et al, 2002). The improvement of psychopathology, especially the PANSS negative score during the trial, is remarkable but not completely unusual.…”
Section: Panss Scorementioning
confidence: 97%
“…There were 14 trials in which olanzapine was compared with atypical antipsychotic treatments: Beasley 1999, 176,177 Fleming 1998, 70 Oliemeulen 2000, 109 HGCF 2001 (Eli Lilly), Bitter 1999 (clozapine), 74 Jones 1998, 180 Littrell 1999, 154 Tran 1997, 171 Kolff 2000, 152 Malyarov 1999, 153 Conley 2001, 161 Gureje 1998 (risperidone), 186 Lecrubier 1999 (amisulpride), 42 Study R-0548 (ziprasidone: Pfizer, commercial-inconfidence).…”
Section: Olanzapine Versus Atypical Antipsychotic Drugsmentioning
confidence: 99%
“…In the original review, 23 studies were identified for inclusion: Blin 1996, 251 Borison 1991, 252 Bouchard 1998, 253 Ceskova 1993, 254 Chouinard 1993, 255 Claus 1991, 256 Emsley 1995, 257 Hoyberg 1993, 258 Huttunen 1995, 259 Mahmoud 1998, 260 Marder 1994, 116 Mesotten 1991, 261 Min 1993, 262 Peuskens 1995, 263 Fleurot 1997, 62 Bondolfi 1998, 110 Anand 1998, 111 Breier 1999, 112 Wahlbeck 2000, 113 Tran 1997, 171 Klieser 1996, 264 Jones 1998, 193 Gureje 1998. 186 Data extraction sheets for these studies are presented in appendix 3.…”
Section: Old Rctsmentioning
confidence: 99%
“…To assess treatment-emergent parkinsonism, the proportion of patients with a Simpson-Angus total score Ͼ 3 during the 24-h study period was calculated from among those with a total score р 3 at baseline. This definition was established a priori and has been used in previous olanzapine studies (Sanger et al 1999;Tran et al 1997). Kaplan-Meier estimates of time to response on the PANSS-EC during the 2 h post first injection were compared among treatment groups using a logrank test.…”
Section: Methodsmentioning
confidence: 99%